2021
DOI: 10.1292/jvms.20-0713
|View full text |Cite
|
Sign up to set email alerts
|

Species-barrier on the cross-species oral transmission of bovine AA amyloidosis in mice

Abstract: In AA amyloidosis, cross-species oral transmission has been demonstrated in several animal models. While it is known that the transmission efficiency of AA amyloidosis between different species is lower than that among the same species, the mechanism of this species-barrier is unclear. In this study, we found at first that mice orally given a large amount of bovine AA simultaneously with inflammatory stimulation did not develop AA amyloidosis. Therefore, we hypothesized that the low efficiency of the cross-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…In prion diseases, prion proteins absorbed and phagocytosed by PP are thought to reach the spleen through mesenteric lymph nodes [ 16 ]. We also previously demonstrated that AA administered in mouse PP migrated to other lymphoid tissues, indicating that amyloid absorbed in the gastrointestinal tract may be transferred through the lymphatic system [ 17 ]. In this study, the PP, which is rich in immune cells [ 18 ] may be more likely to transport the AEF via the lymphatic system than the stomach wall, leading to the spread of amyloid deposits.…”
Section: Discussionmentioning
confidence: 99%
“…In prion diseases, prion proteins absorbed and phagocytosed by PP are thought to reach the spleen through mesenteric lymph nodes [ 16 ]. We also previously demonstrated that AA administered in mouse PP migrated to other lymphoid tissues, indicating that amyloid absorbed in the gastrointestinal tract may be transferred through the lymphatic system [ 17 ]. In this study, the PP, which is rich in immune cells [ 18 ] may be more likely to transport the AEF via the lymphatic system than the stomach wall, leading to the spread of amyloid deposits.…”
Section: Discussionmentioning
confidence: 99%